2018
DOI: 10.5194/tc-2018-248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of blowing snow particles in images from a multi-angle snowflake camera

Abstract: Abstract. A new method to automatically discriminate between hydrometeors and blowing snow particles on Multi-Angle Snowflake Camera (MASC) images is introduced. The method uses four selected descriptors related to the image frequency, the number of particles detected per image as well as their size and geometry to classify each individual image. The classification task is achieved with a two components Gaussian Mixture Model fitted on a subset of representative images of each class from field campaigns in Ant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Furthermore, Grazioli et al () reported that MASC measurements at DDU are contaminated by blowing snow. To solve this issue, Schaer et al () used a Gaussian mixture model to discriminate between precipitation and blowing snow images in MASC data. As Polar WRF does not account for blowing snow in its current set of parameterizations, removing blowing snow from MASC data makes it possible to directly compare precipitation PSDs between the model and the MASC.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Grazioli et al () reported that MASC measurements at DDU are contaminated by blowing snow. To solve this issue, Schaer et al () used a Gaussian mixture model to discriminate between precipitation and blowing snow images in MASC data. As Polar WRF does not account for blowing snow in its current set of parameterizations, removing blowing snow from MASC data makes it possible to directly compare precipitation PSDs between the model and the MASC.…”
Section: Methodsmentioning
confidence: 99%
“…One challenge during measurements of snowflakes in free-fall is the contamination from blowing snow. Schaer et al (2018) developed a method to automatically identify blowing snow particles in MASC images. Despite the presence of a double fence wind shield during ICE-POP 2018, 31 % of the particles were identified as blowing snow and removed for this study.…”
Section: Multi-angle Snowflake Cameramentioning
confidence: 99%
“…Variables derived from the high-resolution images include those describing a hydrometeor's size, shape, fall orientation, and approximate riming degree (Garrett et al, 2012;Garrett and Yuter, 2014;Garrett et al, 2015). As these hydrometeor properties are crucial for accurate numerical modeling and microwave scattering calculations, the MASC has been used at various polar and mid-latitude locations to constrain microphysical characteristics (Garrett et al, 2012;Garrett and Yuter, 2014;Garrett et al, 2015;Grazioli et al, 2017;Kim et al, 2018;Dunnavan et al, 2019;Jiang et al, 2019;Kim et al, 2019;Vignon et al, 2019), improve radar-based estimates of snowfall rates (Gergely and Garrett, 2016;Cooper et al, 2017;Schirle et al, 2019), automatically classify hydrometeors (Praz et al, 2017;Besic et al, 2018;Hicks and Notaroš, 2019;Leinonen and Berne, 2020;Schaer et al, 2020), reconstruct particle shapes (Notaroš et al, 2016;Kleinkort et al, 2017) and size distributions (Cooper et al, 2017;Huang et al, 2017;Schirle et al, 2019), and as ground truth comparisons for radar measurements (Bringi et al, 2017;Gergely et al, 2017;Matrosov et al, 2017;Kennedy et al, 2018;Oue et al, 2018;Matrosov et al, 2019). Unlike more common precipitation gauges, the wind velocity field in the proximity of the MASC has not been simulated for various surface winds speeds, directions, or turbulence kinetic energies (TKE).…”
mentioning
confidence: 99%